IS IT NECESSARY TO REMOVE INTRAPAPILLARY DUCTS IN THERAPEUTIC MAMMARY ADENECTOMIES FOR BREAST CANCER? - Heinzen, Rebeca Neves; Barros, Alfredo Carlos Simões Dornellas de; Carvalho, Filomena Marino; Nimir, Cristiane da Costa Brandeia Abrahao; Jacomo, Alfredo Luiz (Mastology, 2020)
Introduction: The nipple-areola complex (NAC) has glandular tissue in intrapapillary ducts (IPDs). When the NAC is preserved during mammary adenectomies (MA) for the treatment of breast cancer (BC), this glandular tissue, which is a potential focus of tumor residues, remains. Objective: To estimate the frequency of neoplastic development in IPDs among BC patients treated with MA. Method: After the MA and with evidence of free retroareolar margin through intraoperative examination, the nipple was inverted, and its central portion, where mammary ducts are located, removed. A pointed-tip scalpel was used, preserving a tissue rim of 1.0 to 2.0 mm. The analysis involved 219 cases submitted to this type of sur-gery in the Clínica Professor Alfredo Barros. In all patients, the distance tumor-NAC was ≥2.0 cm, according to magnetic resonance imaging (MRI). The intrapapillary tissue removed was sent for microscopic examination of sections embedded in paraffin. Results: We found 4 cases of ductal carcinoma in situ (none infiltrating) in IPDs (1.19%). Considering only the 217 cases with free retroareolar margin in the definitive examination, the number of patients with ductal carcinoma in situin IPDs decreased to 2 (0.9%). Conclusion: IPDs are rarely involved in selected cases of MA (distance tumor-NAC≥2.0 cm on MRI and free retroareolar margin). Ideally, they should be removed, especially when the intent is avoiding radiotherapy.